Attenuation of Gouty Arthritis by Emodinol in Monosodium Urate Crystal-Treated Mice - Chen, Lvyi; Lan, Zhou; Ma, Shuwei; Zhao, Ling; Yang, Xinzhou (Planta Medica, 2013)
A series of studies have recently demonstrated that the release of interleukin 1β induced by monosodium urate crystals is central to the experimental gouty arthritis. Elaeagnus pungens has been traditionally used for the treatment of gouty arthritis in China for more than thousands years. However, there is still little known about the active ingredients and mechanisms of E. pungens against gouty arthritis. Emodinol, as a major triterpene compound in E. pungens, has been seldom reported to have an effect on gouty arthritis. Therefore, the potential beneficial effects and mechanisms of emodinol on gouty arthritis were investigated in this study. Results showed that it significantly ameliorated the hyperalgesia, inflammation, and levels of multiple proinflammatory cytokines in monosodium urate crystals-treated mice. These findings elucidate that emodinol exhibits a prominent effect on improving symptoms of acute gouty arthritis induced by monosodium urate crystals through inhibiting the generation of proinflammatory cytokines.
Keywords: Elaeagnus pungens; Elaeagnaceae; emodinol; gouty arthritis; interleukin 1β; monosodium urate crystals